Analysıs Of Turnover Intentıon Through Career Development And Employee Workload In Jakarta Indonesıa - Fiona Thedja; I Gede Adiputra (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
Human resources have an important role. Human resources determine the success of an organization or company. Other resources are also very dependent on human resources, so human resources must be considered and managed properly by the company. The purpose of this study is to examine the effect of career development and workload on employee turnover intention in Jakarta. The population used in this study were male and female employees or employees working in Jakarta and the method used in sampling was purposive sampling of 100 respondents, data analysis techniques using SmartPLS ver 4.0. The results of this study indicate that career development has a significant negative effect on turnover intention and workload has a significant positive effect on employee turnover intention in Jakarta.